Social Support and Psychosocial Resilience: Evaluating the Impact of Community-Based Interventions on Mental Health - Ekayani, Syafira Putri; Cahyono, Maria Yuni Megarini; Adiawaty , Susi (Indonesian Scientific Publication, 2025)
Mental health remains a critical global concern, particularly in settings where structural and social disparities limit access to appropriate care. This narrative review aims to examine the effectiveness of social support interventions—both interpersonal and community-based—in promoting mental well-being and reducing psychological distress. Using an integrative approach, literature was collected from academic databases such as Scopus and Google Scholar, utilizing key terms including